Impact of anarchic urbanisation on the organisation of the transport system To Tizi Ouzou - Louani, Kahina.; KEBICHE , Abdelhakim (Journal of Human Sciences, 2021)
The massive legal or informal urbanization, the strong population surge and the rural exodus, are the most significant events in the history of Tizi Ouzou (T. O) since independence to the present day. We will study through this article the various obstacles of the urbanization process, the dysfunctions of the transport system and we will highlight the key factors that have generated the increase of daily mobility in the city of T. Ô, based on the majority of the results obtained from the household displacement survey (EMD) carried out among households in the city of (T. O) in 2016.